The doctrine of national interest in Spanish PIL nowadays - Arenas García, Rafael (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
Domestic law in many countries and several international instruments apply the doctrine of national interest. This work examines the role it plays, what conditions must be met for it to operate and how it is regulated both in the Rome I Regulation and in the Spanish domestic Private International Law. The recent reform of art is also analysed. 10.8 of the CC, which has profoundly transformed the regulation of this doctrine in the Spanish domestic Private International Law.
Keywords: Legal capacity; international contracts; Rome I Regulation; doctrine of national interest